EFFECT OF EXTRACTION TECHNIQUE OF RUTA GRAVEOLENS ON ANTITYROSINASE ACTIVITY AND CORRELATION AMONGST INHIBITORY ACTIVITY, PHENOLIC COMPOUNDS CONTENT AND CYTOTOXICITY - MUÑOZ D., Katalina; LONDOÑO L., Julián A.; ARANGO A., Gabriel J.; SIERRA R., Jelver A.; BRAVO M., Karent E. (Vitae, 2009)
Skin pigmentation is the consequence of melanin production and dispersion, this pigment is formed by a successive oxidation of L-Tyrosine into L-Dihydroxyphenylalanine (L-DOPA) and dopaquinone by Tyrosinase enzyme. Skin pigmentation irregularities become an aesthetic problem for many people. Therefore there is a big interest in research on products with skin lightening properties. In order to find inhibitors of Tyrosinase enzyme from natural product, extracts of Ruta graveolens (R. graveolens) were studied by using different extraction methods. The inhibition of the oxidation of L-Tyrosine catalyzed by mushroom tyrosinase is determined and correlated with cytotoxicity and the content of phenolic compounds, because inhibitory activity on the enzyme has been reported of these kind of compounds. It was found that the extraction method affects strongly the content of phenolic compounds of the extract and the cytotoxicity as well, in contrast with the inhibition of tyrosinase activity which remains almost unaffected.